Effect of dietary addition of dried whey and/or copper sulfate on starter pig performance - R C Thaler; M E Johnston; G L Allee; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1986)
Two 35-day trials involving 504 pigs were conducted to determine the efficacy of dietary supplementation of copper sulfate (CuS04) and/or dried whey to corn-soybean meal starter pig diets (1.25% lysine). Pigs were weaned at 21+3 days and ranged in average initial weight from 8.1 to 19.2 lbs. In trial 1, CuSO4 addition of either 0 or 250 ppm were made to diets containing 0, 10, and 20% extra-grade dried whey. At both 2 and 5 weeks, average daily gain (ADG), average daily feed intake (ADFI), and feed efficiency (F/G) improved linearly (P<.05) with increasing whey levels. Also, CuSO4 additions of 250 ppm increased ADG and ADFI (P<.05) at 2 and 5 weeks. The six dietary treatments in trial 2 consisted of a negative control (no CuSO4 or dried whey), and five other diets containing 250 ppm CuS04: with graded levels of dried whey (0, 5, 10, 15, and 20%). Dried whey additions linearly increased ADG and ADFI at both 2 and 5 weeks (P<.05), whereas F/G at 2 and 5 weeks was optimized at the 5% dried whey level. Copper sulfate supplementation improved ADG and F/G at 5 weeks (P<.05). These results suggest that CuS04 additions are beneficial for starter pig performance, and the 5% dried whey addition gave starter pig performance equal to that with 20% dried whey addition, when CuSO4 was present in both diets.; Swine Day, Manhattan, KS, November 20, 1986
Keywords: Swine day; 1986; Kansas Agricultural Experiment Station contribution; no. 87-133-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 507; Swine; Dried whey; Copper sulfate; Starter pig